Functional outcomes after combined iris and intraocular lens implantation in various iris and lens defects - Mayer, Christian; Hoffmann, Andrea M.; Prahs, Phillipp; Reznicek, Lukas; Khoramnia, Ramin (BMC ophthalmology, 2020)
To assess the functional outcomes after combined iris and intraocular lens (IOL) repair in aniridia patients.
Gesehen am 15.10.2020